Perbedaan Brain Gym dan Puzzle Therapy terhadap Fungsi Kognitif Lansia - Indra Nur Azizah; Siti Juwariyah; Prita Adisty Handayani (Indonesian Journal of Nursing Research (IJNR), 2026)
Cognitive function is an imporotant aspect of elderly life that is vulnerable to decline due to the aging process. The decline may affect the ability to think, remember, and solve problems, making appropriate interventions assential to maintain and improve cognitive function. Brain Gym and Puzzle Therapy are non-pharmacological intervention used to stimulate cognitive function in the elderly. This study aims to determine the difference between Brain Gym and Puzzle Therapy on the cognitive function of the elderly. This is a quantitative study using a pre-experimental design with a one-group pre-test and post-test approach, conducted at Panti Wening Werdoyo Ungaran from April 14 to 26, 2025. The sample consisted of 60 elderly participants selected using purposive sampling, with 30 responden in the Brain Gym group and 30 in the Puzzle Therapy group. Cognitive function was measured using the Indonesian version of the Montreal Cognitive Assesment (MoCA-Ina). Bivariate anaysis in this study used the Wilcoxon test and the Mann-Whitney test. The Mann-Whitney test showed a significant difference (p = 0,041), with greater improvement in cognitive function in the Brain Gym group. The improvement in cognitive function was observed in the delayed recall aspect, which was more optimally enhanced in the Brain Gym group compared to the Puzzle Therapy group. Based on the result of this study, it can be concluded that Brain Gym is more effective in improving cognitive function in the elderly.   Abstrak Fungsi kognitif merupakan aspek penting dalam kehidupan lansia yang rentan mengalami penurunan seiring proses penuaan. Penurunan ini dapat memengaruhi kemampuan berpikir, mengingat, serta memecahkan masalah, sehingga diperlukan intervensi yang tepat untuk menjaga dan meningkatkan fungsi tersebut. Brain Gym dan Puzzle Therapy merupakan intervensi nonfarmakologis yang digunakan untuk menstimulasi fungsi kognitif pada lansia. Penelitian ini bertujuan mengetahui perbedaan antara Brain Gym dan Puzzle Therapy terhadap fungsi kognitif lansia. Jenis penelitian ini kuantitatif dengan desain penelitian yang digunakan yaitu pre-eksperimental dengan pendekatan one group pre-test and post-test, yang dilaksanakan di Panti Wening Wardoyo Ungaran pada tanggal 14–26 April 2025. Sampel dalam penelitian ini berjumlah 60 lansia yang dipilih menggunakan teknik purposive sampling, terdiri dari 30 responden kelompok Brain Gym dan 30 responden kelompok Puzzle Therapy. Pengukuran fungsi kognitif menggunakan instrumen Montreal Cognitive Assessment versi Indonesia (MoCA-Ina). Uji bivariat dalam penelitian ini menggunakan uji Wilcoxon dan uji Mann-Whitney. Hasil uji Mann-Whitney menunjukkan perbedaan signifikan (p = 0,041), dengan peningkatan fungsi kognitif lebih tinggi pada kelompok Brain Gym. Peningkatan fungsi kognitif terlihat pada aspek delayed recall yang lebih optimal pada kelompok Brain Gym dibandingkan kelompok Puzzle Therapy. Berdasarkan hasil penelitian tersebut, dapat disimpulkan bahwa Brain Gym lebih efektif dalam meningkatkan fungsi kognitif lansia.